Optimization of Early Detection of Motor Vehicle Theft Crimes by Bandarlampung Police Intelligence Unit - Reza Rahmat Mulya (Indonesian Journal of Police Studies, 2021)
The background of this research arises because of the high number of cases of theft of motor vehicles in the jurisdiction of bandarlampung police which continues to increase every year. This must be taken to reduce and even eliminate the criminality of theft of motor vehicles in bandarlampung city. Bandarlampung Police Intelligence Unit is tasked to carry out early detection to prevent the occurrence of cases of theft of motor vehicles. The purpose of this study is to describe an overview of how the implementation of early detection, what faktors affect the implementation of early detection, and how optimizations made by the Bandarlampung Police Intelligence Unit in early detection of criminal theft of motor vehicles. As an analysis review to discuss this study, researchers used several concept theories, namely management theory, routine activity theory, optimization concept, intelligence concept, early detection concept, and curanmor concept. This research was conducted with a qualitative approach that seeks to obtain a more in-depth picture of a phenomenon by using data collection techniques in the form of interviews, observations, and document studies. The results showed that early detection of motor vehicle theft crimes still has to be improved because the high number of motor theft cases is still high and increases every year, this is influenced by several supporting faktors and inhibitions both internal and external. From internal faktors, among others related to human resources members, as well as facilities and infrastructure, while external faktors include the condition and negligence of the community itself and coordination of each technical function of the police is not good. Advice from the author for bandarlampung police (1) so that Satintelkam members can optimize the gathering of intelligence networks and the public (2) increasing quantity and quality of human resources and improve facilities and infrastructure (3) optimize the implementation of tasks by the head of the Unit or unit.